Examining the impact of land use on flood losses in Seoul, Korea. (January 2018) - Lee, Yoonjeong; Brody, Samuel D.
Abstract: Floods have been the costliest and most disruptive of all natural hazards worldwide. In particular, urban flooding continues to be a concern for both developed and developing countries. Increasing physical risk associated with environmental changes combined with rapid land use change and development make many urban areas more vulnerable to floods. Floods are not solely based on hydro-meteorological conditions, but also result from human activities such as unplanned land use or haphazard development. While there is a growing body of research focused on understanding the impacts of land use on flood impacts in the United States, little empirical research has been conducted outside of the country although many other nations experience flooding. In particular, many countries in south and east Asia have undergone rapid urbanization concurrent with industrialization and population growth, resulting in worsening flood problems over time. To address this knowledge gap, this study examines the factors contributing to flood loss in Seoul, Korea, with a particular focus on land use status and change. Panel regression models are analyzed using actual flood loss data for Seoul from 2003 to 2012. Results indicate that urban built-up land with higher impervious surfaces and agricultural land may cause more flood damage than other land uses analyzed in the study. However, a high density development of compact design can decrease flood loss. These results indicate the importance of resilient land use planning in urban areas. Overall, this study provides insights to planners and decision makers about how they can effectively reduce flood risk and associated adverse impacts.